Patterns and Marketing Strategies of Herbal Medicine at Sukoharjo Regency - Purnaningsih, Ninuk; Saraswati, Yudhistira; Anggrasari, Herdiana (Jurnal Jamu Indonesia, 2024)
The development of the herbal industry, especially in the sector of herbal medicine, is increasingly gaining momentum. The COVID-19 pandemic has heightened the demand for a healthy life. Consequently, many institutions are involved in the marketing and distribution of herbal products. This study aimed to analyze the institutions involved, marketing patterns, and marketing strategies for industrially processed herbal medicine products. A qualitative approach with descriptive analysis was employed in this study. Data collection methods included observation, literature study, and interviews with informants. The key informants in this research included herbal medicine business actors and market managers. These business actors consist of herbal medicine processors and marketers. This research was conducted in Sukoharjo Regency. The results show that the institutions involved in the marketing chain of herbal medicine products comprise raw material suppliers, manufacturers functioning as distributors, retailers, and consumers. The marketing chain for processed herbal medicine products can be categorized into 6 marketing channels. The marketing strategies for industrially processed herbal medicine products that can be implemented include promotion via social media; employing a super value strategy; adding distribution agents; developing research on standardization and market opportunities; and innovation in industrially processed herbal medicine products.